The invention in the criticism of the Andalusian Muwashah - عبدالمنعم عزيز النصر (College of Education for Women, 2019)
The research has arrived to the following results: 1. There were critical views that accompanied the beginnings of (Muwashah). These views were derived from literary criticism that handled the ancient Arabic poetry, especially its kinds that were concerned with artificiality in addition to the views based on rivalry among makers of (Muwashah) in front of the audience so as to judje who is the best according to artistic response. 2. There existed new critical views, their originality was shown through the new critical theories that appeared especially those concerned with receiving the text and reading theory. 3. The Muwashah was one of the most important poetic arts that reproduced previous text, not in the traditional from which used implication or guotation, but in the creative form and this was supported by Sufi Washaheen who set out in their Sufi texts from the special theory of listening adopted by the Sufi doctrine. And thus some of their pieces of Muwashah responded to the theorizing that took place about the inter text nality theory that especially adopts creative texts, and was one of the sublime models that enriched our Arabic literature.